MLXIPL variant in individuals with low and high triglyceridemia in white population in Central Europe - Vrablik, Michal; Ceska, Richard; Adamkova, Vera; Peasey, Anne; Pikhart, Hynek; Kubinova, Ruzena; Marmot, Michael; Bobak, Martin; Hubacek, Jaroslav A (Human genetics, 2008)
We tested the hypothesis that the MLXIPL rs3812316 variant predicts plasma triglyceride (TG) levels. We compared three groups of adult individuals: 162 persons with TG > 10 mmol/L, 266 persons with TG < 0.65 mmol/L, and 2,043 population-based controls (range of TG concentrations 0.7-8.7 mmol/L). We found a small difference in the frequency of the Gln allele carriers between population controls (20.4%) and persons with low TG (26.3%, P = 0.033). We found no difference between individuals with high TG and population controls, and there was no association between the MLXIPL variant and plasma TG levels among the population controls.
Keywords: Amino Acid Substitution; Triglycerides; Polymorphism, Single Nucleotide; hypertriglyceridemie; Humans; sekvence nukleotidů; Case-Control Studies; lidé středního věku; běloši; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; studie případů a kontrol; jednonukleotidový polymorfismus; Female; Aged; dospělí; frekvence genu; White People; senioři; lidé; Genotype; Hypertriglyceridemia; genetická variace; DNA; Genetic Variation; Adult; triglyceridy; ženské pohlaví; Base Sequence; Male; substituce aminokyselin; Middle Aged; Czech Republic; Gene Frequency; genotyp; transkripční faktory BHLH-Zip; Česká republika; mužské pohlaví